Hubungan Pemberian ASI Eksklusif Dengan Kejadian Stunting Pada Balita - Sr. Anita Sampe SJMJ; Rindani Claurita Toban; Monica Anung Madi (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Stunting is a chronic malnutrition problem caused by nutrient intake that is not in accordance with nutritional needs. One of the causes of stunting in children is exclusive breastfeeding is not given during six months because breast milk is needed during in baby’s growth period so that the nutritional needs are fulfilled. The purpose of this study was to determine the correlation of exclusive breastfeeding with the incidence of stunting in children. The design of this study was a case-control study approach on 144 respondents consisting of 72 case respondents and 72 control respondents, respondents were parents of children who were diagnosed with stunting and non-stunting. A sampling of this study using a cluster random sampling approach. Instruments is questionnaires and mechanical measuring. The results of this study used chi-square test and odds ratio test. Chi-square test results obtained p = 0.000 (0.000 < 0.05), this shows there is a correlation of exclusive breastfeeding with the incidence of stunting in children. While in the odds ratio test the value of R = 61 which means that children who are not exclusively breastfed are 61 times more likely to experience stunting than children who are exclusively breastfed. Exclusive breastfeeding for babies so as to reduce the risk of stunting.